Cell entry, efficient RNA replication, and production of infectious hepatitis C virus progeny in mouse liver‐derived cells. Issue 1 (18th November 2013) - Frentzen, Anne; Anggakusuma,; Gürlevik, Engin; Hueging, Kathrin; Knocke, Sarah; Ginkel, Corinne; Brown, Richard J.P.; Heim, Markus; Dill, Michael T.; Kröger, Andrea; Kalinke, Ulrich; Kaderali, Lars; et al.
<x xml:space="preserve">Abstract</x> Only humans and chimpanzees are susceptible to chronic infection by hepatitis C virus (HCV). The restricted species tropism of HCV is determined by distinct host factor requirements at different steps of the viral life cycle. In addition, effective innate immune targeting precludes efficient propagation of HCV in nonhuman cells. Species‐specificity of HCV host factor usage for cell entry and virus release has been explored. However, the reason for inefficient HCV RNA replication efficiency in mouse liver cells remains elusive. To address this, we generated novel mouse liver‐derived cell lines with specific lesions in mitochondrial antiviral signaling protein (MAVS), interferon regulatory factor 3 (IRF3), or Interferon‐α/β receptor (IFNAR) by in vivo immortalization. Blunted innate immune responses in these cells modestly increased HCV RNA replication. However, ectopic expression of liver‐specific human microRNA 122 (miR‐122) further boosted RNA replication in all knockout cell lines. Remarkably, MAVS−/−miR‐122 cells sustained vigorous HCV RNA replication, attaining levels comparable to the highly permissive human hepatoma cell line Huh‐7.5. RNA replication was dependent on mouse cyclophilin and phosphatidylinositol‐4 kinase III alpha (PI4KIIIα) and was also observed after transfection of full‐length viral RNA. Additionally, ectopic expression of either human or mouse apolipoprotein E (ApoE) was sufficient to permit release of infectious particles. Finally, expression of human entry cofactors rendered these cells permissive to HCV infection, thus confirming that all steps of the HCV replication cycle can be reconstituted in mouse liver‐derived cells. Conclusion: Blunted innate immunity, abundant miR‐122, and HCV entry factor expression permits propagation of HCV in mouse liver‐derived cell lines. (Hepatology 2014;58:78–88)